»Es ist nur ein Dorf« Schwetzingen mit den Augen Leopold Mozarts. Begleitpublikation zur Ausstellung im Karl-Wörn-Haus, Museum der Stadt Schwetzingen, vom 28. April - 28. Juli 2019 aus Anlass des 300. Geburtstages des Komponisten - Thomsen-Fürst, Rüdiger (Schriften zur Südwestdeutschen Hofmusik, 2020)
This volume, which accompanies the exhibition of the same name, honours Leopold Mozart (1719-1787), who was not only a musician, composer and teacher, but also a well-informed observer of his time. His letters contain numerous details on music and cultural-historical themes, and his notes on his stay in the summer residence of Schwetzingen in the Palatinate are invaluable. The authors investigate this information and relate it to the knowledge of their respective disciplines. The result is a comprehensive picture of the Electoral Palatinate summer residence of 1763, a music-historical focal point in the third quarter of the eighteenth century